A Test for Moral Hazard in the Labor Market: Contractual Arrangements, Effort, and Health - Foster, Andrew D.; Rosenzweig, Mark R. (The Review of Economics and Statistics, 1994)
Andrew D. Foster, Mark R. Rosenzweig, A Test for Moral Hazard in the Labor Market: Contractual Arrangements, Effort, and Health, The Review of Economics and Statistics, Vol. 76, No. 2 (May, 1994), pp. 213-227